2000
DOI: 10.1046/j.1365-3040.2000.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cytokinin levels in transgenic PSAG12IPT tobacco plants have large direct and indirect effects on leaf senescence, photosynthesis and N partitioning

Abstract: We studied the impact of delayed leaf senescence on the functioning of plants growing under conditions of nitrogen remobilization. Interactions between cytokinin metabolism, Rubisco and protein levels, photosynthesis and plant nitrogen partitioning were studied in transgenic tobacco (Nicotiana tabacum L.) plants showing delayed leaf senescence through a novel type of enhanced cytokinin syn‐thesis, i.e. targeted to senescing leaves and negatively auto‐regulated (PSAG12–IPT), thus preventing developmental abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
114
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 39 publications
(70 reference statements)
14
114
1
10
Order By: Relevance
“…n p 12 reported for solitarily grown SAG plants (Gan and Amasino 1995;Wingler et al 1998;Jordi et al 2000), we also observed a higher LAI (table 2) and more uniform N distribution ( fig. 2D) of SAG plants compared to WT plants in the dense leaf canopies, allowing us to test these model predictions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…n p 12 reported for solitarily grown SAG plants (Gan and Amasino 1995;Wingler et al 1998;Jordi et al 2000), we also observed a higher LAI (table 2) and more uniform N distribution ( fig. 2D) of SAG plants compared to WT plants in the dense leaf canopies, allowing us to test these model predictions.…”
Section: Discussionsupporting
confidence: 75%
“…Wisconsin 38) and transgenic hemizygous P SAG12 -IPT (SAG) tobacco (Gan and Amasino 1995;Jordi et al 2000).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P SAG12 :IPT plants retained their leaves longer than WT plants as expected based upon previous observations (Boonman et al, 2006;Jordi et al, 2000;Gan & Amasino, 1995). The difference between the total number of nodes on the stem, a measure of all the leaves that had ever been produced, and the live leaves present at the time of the harvest is a measure of the number of leaves that had been lost in the canopy due to senescence and abscission ( Table 2).…”
Section: Resultssupporting
confidence: 77%
“…Canopy recycling of N L is particularly important for plants grown in nitrogen poor soils. Jordi et al (2000) demonstrated the detrimental effects of prolonged leaf lifespan on N L and photosynthesis in upper canopy leaves of WT and P SAG12 :IPT plants grown under N-starvation conditions. As in the present study, Jordi et al (2000) found that older leaves in WT plants dried, yellowed, and abscised whereas older leaves on the P SAG12 :IPT plants remained intact, green, and photosynthetically competent.…”
Section: Resultsmentioning
confidence: 94%